ANALISIS BIBLIOMETRIX PERAN PEREMPUAN DALAM PENDIDIKAN ISLAM PADA DATABASE SCOPUS TAHUN 2012-2022 - Ulfatun Naili Nadhiroh; Abdul Halim; Syahrul Ramadhan (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2023)
This study aims to analyze research trends related to the role of women in Islamic education in various parts of the world which were published through the Scopus database from 2012 to 2022. This study used quantitative research methods with bibliometric analysis using R-Packages software and WebInterface Biblioshiny for analysis. and data visualization. The keywords used are 'Islamic Education', and 'Women', to generate more specific data searches with research theme categories. Based on the search results, the researcher obtained 674 scientific papers, which the authors specified using only two types of documents, namely articles and conference papers, resulting in 279 documents. The results of the study show that the theme of the role of women in Islamic education still attracts attention for research to date, even though it fluctuates every year. The most influential publication is research conducted by Noorbala A entitled